Creating an Agenda for Black Birth Equity: Black Voices Matter (Mary Ann Liebert, 2023)
Background: The grim inequity that Black women and infants are more than twice as likely to die during birth than their white counterparts is a public health crisis. Methods: Guided by principles of critical race theory, we used content analysis to analyze the themes of the presentation made by five Black community members on a 2020 Juneteenth panel, a holiday celebrating the emancipation of those who had been enslaved in the United States. Results: Panelists sparked the conversation by unpacking the traumatic experiences of health inequities and structural racism on Black families and diverse caregivers. As a part of qualitative content analysis, four major themes emerged: (1) the matrix of domination, (2) specific oppressions of the health care system, (3) empowerment reconceptualized, and (4) dimensions of racism. Participants also discussed how racial disparities may have exacerbated the complexities and challenges of elevating Black voices and creating birth equity. Discussion: Based on Black families' experiences, four areas must be addressed: health care system's policies of oppression that create barriers to listening to Black women, reconceptualizing retention for providers of color and support for Black women and their families, and racism.